An Analysis on Pre-sequences in Making Invitation Used by freshmen of English as a Foreign Language: The Pragmatics Perspective - Hidayat, Yusuf (Journal of English Teaching and Learning Issues, 2019)
This study reports the nature of making invitation carried out by freshmen students of the pragmatic point of view. It attempts to investigate the pre-sequences strategies used for the purpose of inviting in freshmen.  The respondents themselves were chosen from the English Education Program, a certain private university located in Ciamis, West Java Province. The results asserted that based on the data gained in the findings aforementioned, 80% of the respondents express their pre-sequences in the form of saying hello, and asking condition. Meanwhile, 20% of other respondents express their pre-sequences in other expressions. Furthermore, 100% of the respondents express pre-sequences expression in beginning their conversation before inviting their partners. In conclusion, the respondents expressed pre-sequences in beginning their invitation expression. Meanwhile, they are able to express quite proper politeness for inviting, accepting or refusing the invitation such suggested by the theory.